The effect of liquidity and leverage on financial distress with good corporate governanceas a moderating variable in the manufacturing sector on the Indonesian Stock Exchange - Aisyah, Siti; Rokhmawati, Andewi; Fitri, Fitri (Program Pascasarjana, Universitas Riau, 2023)
This study aims to determine the effect of liquidity and leverage on financial distress with good corporate governance as a moderating variable. This type of research is quantitative research. This study includes all manufacturing companies. By using purposive sampling, this study consists of 43 companies. The data processing method used was moderating regression analysis. The results showed that liquidity had a significant negative effect on financial distress. At the same time, leverage has a significant positive impact on financial distress. Good Corporate Governance as a moderating variable can strengthen the influence of the dependent variable on the independent variables in this study.